Intra-patient variability of thromboelastographic parameters following in vivo and ex vivo administration of recombinant activated factor VII in haemophilia patients. A multi-centre, randomised trial - Kenet, Gili; Stenmo, Camilla B.; Blemings, Allan; Wegert, Wolfgang; Goudemand, Jenny; Krause, Manuela; Schramm, Wolfgang; Kirchmaier, Carl; Martinowitz, Uri (Thrombosis and Haemostasis, 2010)
Thromboelastography methods have been used to predict or monitor treatment of haemophilia patients with recombinant activated factor VII (rFVIIa). However, neither of the two thromboelastographic methods (ROTEM and TEG) has as yet been validated. This multi-centre, randomised trial compared both methods in terms of intra- and inter-patient variability following in vivo and ex vivo rFVIIa administration to haemophilia A and B patients with and without inhibitors. Patients (≥16 years old) received the same intravenous rFVIIa dose (45, 90 or 180 μg/kg) twice, 1–12 weeks apart. Blood samples were collected pre-dose and 15, 60, 120 and 240 minutes post-dose for ROTEM and TEG analysis. Pre-dose samples were also spiked ex vivo with rFVIIa (0.6, 1.2 or 2.4 μg/ml), to correspond to the three in vivo doses. Twenty-six haemophilia A and four haemophilia B patients were enrolled. A significant treatment effect was observed with in vivo rFVIIa (p<0.05) with more pronounced effects in inhibitor (n=14) versus non-inhibitor (n=16) patients. There was a strong positive correlation between ROTEM and TEG parameters. Intra- and inter-patient variation was large for all thromboelastography parameters at all time points and rFVIIa doses. Intra-patient variation was generally lower for non-inhibitor than inhibitor patients, and lower following ex vivo spiking versus in vivo rFVIIa administration. In conclusion, there was a clear effect of rFVIIa on all thromboelastography parameters, but the large intra- and inter-patient variability following in vivo rFVIIa administration renders the use of our method unsuitable for dose-response prediction for haemophilia patients in the clinical setting.
Keywords: Thromboelastography, recombinant activated factor VII, haemophilia, ROTEM, TEG